Consensus in stem cell transplantation for pediatric lymphomas - Kuwahara, Cilmara; Breviglieri, Carla Nolasco Monteiro; Milaré, Luiza; Menezes Neto, Osvaldo Alves (JOURNAL OF BONE MARROW TRANSPLANTATION AND CELLULAR THERAPY, 2026)
Lymphomas are the third most common childhood cancer in Brazil. Management is predicated on precise diagnosis and staging through clinical, pathological, molecular, and radiological evaluation. Although the prognosis for pediatric non-Hodgkin and Hodgkin lymphoma has improved markedly, relapsed or refractory cases remain a clinical challenge. For these patients, aggressive chemotherapy followed by autologous or allogeneic hematopoietic cell transplantation serves as a vital salvage strategy. The Pediatric Group of the Brazilian Society of Bone Marrow Transplantation and Cellular Therapy has revised its current consensus, providing updated recommendations for indications and conditioning protocols. This revision also includes the assessment of new therapeutic strategies, including immunotherapy and CAR-T cell therapy, for eligible patients.